Estimation of interleukin-18 in the gingival crevicular fluid and serum of Bengali population with periodontal health and disease - Vineet Nair (Journal of Indian Society of Periodontology, 2016)
Context: Host's immune response elicits cytokines in response to bacterial challenge. We explore role of one such cytokine interleukin-18 (IL-18) in periodontal health and disease. Aims: IL-18 is a pro-inflammatory and tumor suppressive cytokine. Dental literatures suggest that IL-18 might have a role to play in the progression from oral health to periodontal disease. Therefore, this study was undertaken to elucidate the level and role of IL-18 in the gingival crevicular fluid (GCF) and serum of individuals with healthy gingiva, chronic gingivitis, chronic periodontitis, and aggressive periodontitis before and after periodontal therapy. Settings and Design: Eighty individuals chosen for the study were divided into healthy control group (1A), chronic gingivitis (2A), chronic periodontitis (3A), and aggressive periodontitis (4A) with twenty individuals each. Criteria for the division were the subject's gingival index, probing pocket depth, clinical attachment loss, and radiographic evidence of bone loss. Materials and Methods: The individuals underwent treatment (scaling in case of Groups 1A and 2A and scaling and root planing followed by flap surgery in Groups 3A and 4A) to form posttreatment Groups 1B, 2B, 3B, and 4B, respectively. Thus, a total of 160 GCF and 160 serum samples were collected and tested by ELISA.Statistical Analysis Used: Intergroup comparison was done by post hoc Tukey's test. Results: The mean IL-18 concentration was greatest in Group 3A (GCF 144.61 pg/μl, serum 55.12 pg/ml) followed by Group 4A (GCF 98.55 pg/μl, serum 39.06 pg/ml), Group 2A (GCF 22.27 pg/μl, serum 27.73 pg/ml) and lowest (GCF 17.94 pg/μl, serum 11.49 pg/ml) in Group 1A. Posttreatment groups (1B–4B) showed reduction in the mean IL-18 concentration in both GCF and serum. Conclusions: As the inflammation increased, there was a concomitant increase in the level of IL-18 and vice versa following periodontal therapy.